To find the length of the base \( b \) of the isosceles triangle when one of the longer sides \( a \) is given to be 6.3 centimeters, you can use the perimeter equation provided:
\[ 2a + b = 15.7 \]
Given that \( a = 6.3 \) centimeters, you can substitute this value into the equation:
\[ 2(6.3) + b = 15.7 \]
Now, calculate \( 2(6.3) \):
\[ 12.6 + b = 15.7 \]
Next, to solve for \( b \), subtract 12.6 from both sides:
\[ b = 15.7 - 12.6 \]
Calculating that gives:
\[ b = 3.1 \]
Thus, the equation you can use to find \( b \) after substituting \( a = 6.3 \) is:
\[ b = 15.7 - 2a \]
In this specific case, it becomes:
\[ b = 15.7 - 12.6 \]
Resulting in \( b = 3.1 \) centimeters.